Urban Freedom and Alienation in RK Narayan’s The Guide - Sharma, Chhabita (NPRC Journal of Multidisciplinary Research, 2025)
Background: R.K. Narayan's The Guide (1958) explores urban freedom and alienation through the changing lives of characters like Raju and Rosie/Nalini.Methods: Drawing on Georg Simmel's concept of the city's dual nature, the paper interprets Malgudi as a semi-urban space that navigates the characters' freedom and alienation, allowing them to evolve different identities. The protagonist Raju's journey from a tourist guide to a fake holy man and Rosie's journey to Nalini are interpreted using Simmel's idea that city life allows change but can lead to isolation.Results: The study finds that in Malgudi, Raju assumes multiple roles, including those of a businessman, a good lover, and a corrupt prisoner, taking advantage of the opportunities the town offers him. The city shapes Rosie’s identity, transforming her from an ignored wife in a private home to a celebrated artist.Conclusion: This paper concludes that The Guide reveals both the promise and the pain of city life. Malgudi is a place of dreams and disappointments, where freedom and loneliness are inextricably linked.Novelty: This study provides a spatial interpretation of The Guide, highlighting how urban settings influence characters' identities, choices, and relationships. It moves beyond moral or cultural readings of the text, bridging the gap between fictional lives and real city experiences.